Liminal figures in Marina Carr’s Woman and Scarecrow and Emma Dante’s Vita mia - Donohue, Brenda (FOCUS: Papers in English Literary and Cultural Studies, 2012)
This article explores the thematic preoccupation with death and dying in the works of Italian theatre practitioner Emma Dante and Irish playwright Marina Carr. Unlike modern narratives that sharply delineate between life and death, Dante and Carr's writings blur these boundaries, featuring characters who exist in liminal spaces between life and death. Drawing on Victor Turner's theory of liminality, this paper examines these "betwixt and between" characters in two plays: Dante's "Vita mia" and Carr's "Woman and Scarecrow." Both plays challenge and reimagine the conventions of deathbed scenes.